2016
DOI: 10.3928/01477447-20160222-07
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Displaced Acetabular Fractures Using a Modified Stoppa Approach

Abstract: A retrospective evaluation was performed of 36 patients (25 males and 11 females; average age, 44 years) with displaced acetabular fractures who were treated with a modified Stoppa approach. Fractures included 18 anterior columns, 2 both columns, 8 anterior columns with posterior hemitransverse, 6 transverse, and 2 T-type, according to the Judet and Letournel classification. Range of motion, Harris Hip Scores, and Merle d'Aubigné scores were evaluated. Pre- and postoperative measurements taken included displac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
1
15

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 20 publications
3
56
1
15
Order By: Relevance
“…In the patient group of our study, the number of male patients was higher than female patients. Similar to our study, 16 studies on 609 patients to evaluate the Stoppa approach revealed that the male-female ratio was available for 566 patients, which was same as our study [5,[11][12][13][14][15][16][17][18][19][20][21][22][23]. Data for the remaining patients were unavailable due to various reasons.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In the patient group of our study, the number of male patients was higher than female patients. Similar to our study, 16 studies on 609 patients to evaluate the Stoppa approach revealed that the male-female ratio was available for 566 patients, which was same as our study [5,[11][12][13][14][15][16][17][18][19][20][21][22][23]. Data for the remaining patients were unavailable due to various reasons.…”
Section: Discussionsupporting
confidence: 77%
“…The range of age in the 11 studies we cited was 10-88 years [5,[11][12][13][14][15] [11,[16][17][18][19][20]. The mean age in our study was much lower (36.8 ± 8.42 (range 20-73) years) compared to these observations.…”
Section: Discussioncontrasting
confidence: 55%
“…The modi ed Stoppa approach with the lateral window of the classic ilioinguinal approach is practically convenient to access fracture fragments of posterior column effectively with advantages of less blood loss, shorter operation time, and fewer complications than other traditional approaches. The average intraoperative blood loss in our cohorts was 320 mL, which was signi cantly less than blood loss with a single ilioinguinal approach ranging from 760 mL to 1170 [26,29] or simultaneous anterior (Stoppa/iliac window approach) and Kocher-Langenbeck approach ranging from 586 ml to 1252 ml [30][31][32]. Similarly, the average operative time in our cohorts (2.1 hours) is considerably shorter than the single ilioinguinal approach (2.6-4.3 hours) [26,33] and the simultaneous anterior modi ed ilioinguinal/Stoppa approach (2.1-4.4 hours) [30,31,[34][35][36].…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, the afore-mentioned combined anterior approach is practically convenient to access fracture fragments of posterior column effectively with advantages of less blood loss, shorter operation time, and fewer complications than traditional approaches. The average intraoperative blood loss of our cohorts was 320 mL, which was significantly less than blood loss with a single ilioinguinal approach ranging from 760 mL to 1170 [24][25][26] or simultaneous anterior (modified ilioinguinal/Stoppa approach) and Kocher-Langenbeck approach ranging from 586 ml to 1252 ml [26][27][28][29][30]. The average operative time was 2.1 hours in our cohorts, compared with 2.6-4.3 hours for a single ilioinguinal approach [24,25] and 2.1-4.4 hours for the simultaneous anterior (modified ilioinguinal/Stoppa approach) and Kocher-Langenbeck approach [27-29, 31, 32].…”
Section: Discussionmentioning
confidence: 99%